(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian retail industry is at its nascent stage. India, one of the most profitable rising markets, is undergoing a significant transformation in its retail industry. The rise of organised retail outlets in larger and smaller cities in India is the result of the country’s rapid retail development. The goal of current research is to comprehend the notions of retailing and how they have changed over time. This essay discusses the many stages that the retail sector goes through while also addressing the stage that the Indian retail industry is in. The analysis finds that there is a huge potential for Indian and Global retail industry expansion.